Gangguan kepribadian Cluster A dalam anime Oregairu season 1 - Gumelar, Abdul Rohman Agung; Poerbowati, Endang (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
Personality disorders are persistent patterns of behavior, thinking, and experience that influence how individuals interact or socialize with the world and others. In the anime Oregairu (Yahari Ore no Seishun Love Comedy wa Machigatteiru), particularly the main character Hachiman Hikigaya, offers a detailed portrayal of Cluster A personality disorders. According to the DSM-5 (p. 646), Cluster A personality disorders are characterized by odd and eccentric behavior. This study aims to identify and analyze the Cluster A personality disorders exhibited by the main character. The research uses a descriptive qualitative method with a literary psychology approach, focusing on identifying traits that reflect these personality disorders. The main subject of the study is Hachiman Hikigaya, known for his skepticism about others' motives and his reluctance to open up, even to close friends. The study found 5 instances of relevant data: 2 instances of paranoid traits, 2 instances of schizoid traits, and 1 instance of schizotypal traits. The data indicate that Hachiman Hikigaya demonstrates consistent patterns of behavior associated with paranoid personality disorder, evident in his distrust of others' hidden motives, as well as schizoid personality disorder, shown by his avoidance of close relationships and limited emotional expression